Release liner and adhesive article with variable light transmittance
By using release liner and crosslinkable composition in optically transparent adhesive, the balance of mechanical stability and UV barrier function in electronic devices is solved, achieving higher mechanical properties and equipment life.
Patent Information
- Application Number
- CN202380044417.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-05-01
- Publication Date
- 2025-01-10
Smart Images

Figure CN119301210A_ABST
Abstract
Description
Background Art
[0001] In electronic devices such as electronic display devices, pressure sensitive adhesives ("PSAs") are often used to bond cover glass or lenses to the underlying display module of the electronic device, to bond a touch sensor to the cover glass and display, or to bond the lower components of the display to the housing. The pressure sensitive adhesives used in these electronic devices may be optically clear adhesives ("OCAs").
[0002] The presence of the OCA can improve the performance of the display device, for example by increasing brightness and contrast, while also providing structural support for the assembly. For these applications (often referred to as electronic bonding or e-bonding), both the PSA and the OCA should have sufficiently high bond strength to properly maintain good bonding to the assembly, not only when the electronic devices are operated under normal conditions, but also when they are subjected to external forces or extreme environmental conditions. Summary of the invention
[0003] In a first aspect, a release liner is provided. The release liner includes: a substrate having a first major surface and an opposing second major surface; and a release coating disposed on at least a portion of the first major surface of the substrate. The release liner transmits greater average incident light in a wavelength range of 470 nanometers (nm) to 530 nm than in a wavelength range of 400 nm to 460 nm at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°.
[0004] In a second aspect, an adhesive article is provided. The adhesive article comprises the release liner according to the first aspect and an optically clear adhesive disposed on at least a portion of the release liner.
[0005] The above summary of the present disclosure is not intended to describe each disclosed embodiment or each implementation of the present disclosure. The following description more specifically illustrates exemplary embodiments. In several places throughout the application, guidance is provided by example lists, which can be used in various combinations. In each case, the cited list is only used as a representative group and should not be interpreted as an exclusive list. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 is a schematic illustration of a vertical cross-section of an exemplary release liner according to the present disclosure.
[0007] Figure 2 is a schematic illustration of a vertical cross-section of an exemplary adhesive article according to the present disclosure. DETAILED DESCRIPTION
[0008] Glossary
[0009] The term "crosslinkable composition" refers to a reaction mixture that can be crosslinked. The crosslinkable composition can include a polymerizable component and any other materials that can be included in a reaction mixture, such as, for example, free radical initiators, chain transfer agents, antioxidants, solvents, etc.
[0010] The term "curable" means that a solid material can be transformed into a more cross-linked solid by stimulus-induced cross-linking.
[0011] As used herein, the term "gel content" refers to the mass fraction of network material resulting from the polymerization and / or cross-linking process that forms the network.
[0012] The term "aliphatic" refers to C1-C40, suitably C1-C30 straight or branched alkenyl, alkyl or alkynyl groups, which may or may not be interrupted or substituted by one or more heteroatoms such as O, N or S. The term "alicyclic" refers to cyclized aliphatic C3-C30, suitably C3-C20 groups, and includes those interrupted by one or more heteroatoms such as O, N or S.
[0013] The term "alkyl" refers to a monovalent group of a free radical of an alkane and includes straight chain, branched, cyclic and bicyclic alkyl groups and combinations thereof, including both unsubstituted and substituted alkyl groups. Unless otherwise specified, an alkyl group generally contains 1 to 30 carbon atoms. In some embodiments, an alkyl group comprises 1 to 20 carbon atoms, 1 to 10 carbon atoms, 1 to 6 carbon atoms, 1 to 4 carbon atoms or 1 to 3 carbon atoms. The example of an "alkyl" group includes but is not limited to methyl, ethyl, n-propyl, n-butyl, n-pentyl, isobutyl, tert-butyl, isopropyl, n-octyl, n-heptyl, ethylhexyl, cyclopentyl, cyclohexyl, cycloheptyl, adamantyl, norbornyl, etc.
[0014] The term "alkoxy" refers to a radical of the formula -OR a A monovalent group, where R a is an alkyl group as defined above.
[0015] The term "alkylene group" refers to a divalent group that is a free radical of an alkane and includes a straight chain group, a branched chain group, a cyclic group, a bicyclic group, or a combination thereof. Unless otherwise specified, an alkylene group generally has 1 to 30 carbon atoms. In some embodiments, an alkylene group has 1 to 20 carbon atoms, 1 to 10 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms. Examples of "alkylene group" groups include methylene, ethylene, 1,3-propylene, 1,2-propylene, 1,4-butylene, 1,4-cyclohexylene, and 1,4-cyclohexyldimethylene.
[0016] The term "heteroalkane" refers to a divalent group of a heteroalkane (an alkane with a heteroatom in the chain) having at least one catenary O or NH group. Unless otherwise specified, a heteroalkane group typically has 1 to 10 carbon atoms, 2 to 10 carbon atoms, 1 to 6 carbon atoms, 1 to 4 carbon atoms, or 1 to 3 carbon atoms, and up to 6 heteroatoms.
[0017] Each of "alkenyl" and "alkene" refers to a monovalent straight or branched chain unsaturated aliphatic group having one or more carbon-carbon double bonds, such as vinyl.
[0018] The term "aromatic" refers to C3-C40, suitably C3-C30 aromatic groups, including carbocyclic aromatic groups, and heterocyclic aromatic groups containing one or more of the heteroatoms O, N or S and fused ring systems containing one or more of these aromatic groups fused together.
[0019] The term "aryl" refers to a monovalent group that is aromatic and optionally carbocyclic. The aryl group has at least one aromatic ring. Any additional ring can be unsaturated, partially saturated, saturated or aromatic. Optionally, the aromatic ring can have one or more additional carbocyclic rings fused to the aromatic ring. Unless otherwise specified, the aryl group generally contains 6 to 30 carbon atoms. In some embodiments, the aryl group contains 6 to 20 carbon atoms, 6 to 18 carbon atoms, 6 to 16 carbon atoms, 6 to 12 carbon atoms or 6 to 10 carbon atoms. Examples of aryl groups include phenyl, naphthyl, biphenyl, phenanthrenyl and anthracenyl.
[0020] The term "arylidene" refers to a divalent group that is aromatic and optionally carbocyclic. The arylidene has at least one aromatic ring. Optionally, the aromatic ring may have one or more additional carbocyclic rings fused to the aromatic ring. Any additional ring may be unsaturated, partially saturated or saturated. Unless otherwise indicated, the arylidene group often has 6 to 20 carbon atoms, 6 to 18 carbon atoms, 6 to 16 carbon atoms, 6 to 12 carbon atoms or 6 to 10 carbon atoms.
[0021] The term "aralkyl" refers to a monovalent group that is an alkyl group substituted with an aryl group (e.g., as in a benzyl group). The term "alkaryl" refers to a monovalent group that is an aryl group substituted with an alkyl group (e.g., as in a tolyl group). Unless otherwise indicated, for both groups, the alkyl portion often has 1 to 10 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms, and the aryl portion often has 6 to 20 carbon atoms, 6 to 18 carbon atoms, 6 to 16 carbon atoms, 6 to 12 carbon atoms, or 6 to 10 carbon atoms.
[0022] The term "aryloxy" refers to a monovalent group having the formula -OAr, wherein Ar is an aryl group as defined above.
[0023] As used herein, the term "ethylenically unsaturated" refers to a group containing at least one carbon-carbon double bond, including at least one of the following: (1) a vinyl group (CH2=CH-); (2) a (meth)acryloxy group (CH2=CR-(CO)-O-), wherein R is hydrogen or methyl); (3) a (meth)acrylamide group (CH2=CR-(CO)-NH-), wherein R is hydrogen or methyl; or a maleic acid group (-(CO)-(CH=CH)-(CO)-).
[0024] The term "hydrocarbyl" includes aryl and alkyl. "Hydrocarbylene" includes arylene and alkyllene.
[0025] As used herein, the term "(meth)acrylate" is shorthand for acrylate, methacrylate, or a combination thereof, "(meth)acrylic" is shorthand for acrylic, methacrylic, or a combination thereof, and "(meth)acryloyl" is shorthand for acryloyl and methacryloyl groups. "Acryloyl" refers to derivatives of acrylic acid, such as acrylate, methacrylate, acrylamide, and methacrylamide. By "(meth)acryloyl" is meant a monomer or oligomer having at least one acryloyl or methacryloyl group and, if containing two or more groups, connected by an aliphatic segment. As used herein, a "(meth)acrylate functional compound" is a compound that includes, among other things, a (meth)acrylate moiety. The term "(meth)acryloyl" refers to a group having the formula CH2=CR-(CO)-, wherein R is hydrogen (for an acryloyl group) or methyl (for a methacryloyl group). Similarly, the term "(meth)allyl group" refers to a halogenated allyl group and / or an allyl group.
[0026] The term "vinyl" refers to a polymerizable component having the group CH2=CH- but not being part of a (meth)acryloyl group.
[0027] As used herein, "C1," "1C," and "1 carbon" are interchangeable ways of describing a single carbon atom and are used interchangeably when referring to any number of carbon atoms.
[0028] The term "glass transition temperature" (interchangeably written as "T g ”) refers to the glass transition temperature of a homopolymer formed from that monomer. The glass transition temperature of a polymer material is typically measured by dynamic mechanical analysis (“DMA”) at the maximum value of the loss tangent (δ).
[0029] As used herein, the term "optically clear adhesive" refers to an adhesive that exhibits an optical transmittance of at least about 80% of visible light (e.g., 400 nm to 700 nm) measured on a sample having a thickness of about 25 microns to about 250 microns. In some embodiments, the optical transmittance may be at least about 85%, 90%, 95%, or even higher.
[0030] As used herein, the term "transparent" refers to a material having at least 50% transmittance, 70% transmittance, or optionally greater than 90% transmittance in a specific wavelength range, over a wavelength band of at least 30 nanometers (nm), and a thickness of 10 mm or less. Suitable wavelength ranges include, for example, between 200 nm and 400 nm, between 400 nm and 700 nm, or between 700 nm and 1300 nm.
[0031] The term "pressure sensitive adhesive" or "PSA" is used in accordance with the conventional manner of the Pressure Sensitive Tape Committee, which defines known pressure sensitive adhesives as having properties including the following: (1) strong and persistent tack, (2) adhesion with light finger pressure, (3) sufficient ability to remain on an adherend, and (4) sufficient cohesive strength to allow clean removal from an adherend. Materials that have been found to function well as PSAs include polymers designed and formulated to exhibit the desired viscoelastic properties that achieve a desired balance of initial tack, peel adhesion, and shear holding power. PSAs are characterized by being tacky at room temperature (e.g., 20°C). Of great importance to all PSAs is the desired balance of adhesion and cohesion, which is often achieved by optimizing the physical properties of the elastomer, such as the glass transition temperature and modulus. For example, if the glass transition temperature (Tg) or modulus of the elastomer is too high and is above the Dahlquist criterion for tack (3×10 6 Dyne / cm 2 ), the material will not be tacky and cannot be used as a PSA material per se.
[0032] The words "preferred" and "preferably" refer to embodiments of the present disclosure that may provide certain benefits in certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not useful, and is not intended to exclude other embodiments from the scope of the present disclosure.
[0033] In this application, terms such as "a", "an", and "the" are not intended to refer to only a single entity, but include general categories, specific examples of which may be used for illustration. The terms "a", "an", and "the" are used interchangeably with the term "at least one". The phrases "at least one of" and "comprising at least one of" followed by a list refer to any one of the items in the list and any combination of two or more items in the list.
[0034] As used herein, the term "or" is generally used in its ordinary sense, including "and / or," unless the context clearly dictates otherwise. The term "and / or" means one or all of the listed elements, or a combination of any two or more of the listed elements.
[0035] Likewise, all numerical values herein are assumed to be modified by the term "about" and preferably by the term "precisely". As used herein, with respect to the measured amount, the term "about" refers to a deviation in the measured amount that is commensurate with the accuracy of the measurement target and the measurement equipment used as a technician who is careful to measure to a certain extent should be able to expect. In addition, in this article, the numerical range expressed by the endpoint includes all numbers and end values contained in the range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0036] As used herein, as a modifier to a characteristic or property, unless otherwise specifically defined, the term "substantially" means that the characteristic or property will be readily recognizable by a person of ordinary skill, without requiring absolute precision or a perfect match (e.g., within + / -20% for a quantifiable characteristic). Unless otherwise specifically defined, the term "substantially" means a high degree of approximation (e.g., within + / -10% for a quantifiable characteristic), but again does not require absolute precision or a perfect match. Terms such as identical, equal, uniform, constant, strict, etc. should be understood to be within a common tolerance, or within a measurement error applicable to a particular situation, rather than requiring absolute precision or a perfect match.
[0037] Advantages of using optically clear adhesives ("OCAs") in optoelectronic devices can include, among other things, improving light extraction efficiency between the various optical components of the display and reducing light scattering by mitigating refractive index mismatches at interfaces. As the topographical features of optoelectronic device structures evolve into more complex geometries, there is an increasing need to develop highly compliant OCAs that can simultaneously accommodate these complex geometries and mitigate optical defects. However, once the OCA film is integrated into the display, the OCA material should also be mechanically robust over the life of the device in order to provide high mechanical stability and performance. One approach to balancing these potentially opposing manufacturing requirements is to incorporate a latent curing mechanism that can be activated by a user (e.g., typically a display manufacturer) to increase the mechanical stability and performance of the adhesive film after the adhesive film is integrated into the display.
[0038] For some applications, it is also desirable that the OCA material utilizes a UV absorbing additive to protect any UV sensitive components below the OCA layer. For example, a hydroxyphenylbenzotriazole-based UV absorber that exhibits high absorption in light below 400nm wavelengths may be incorporated into the OCA to block UV light from reaching the photosensitive layer adjacent to the adhesive. However, once the adhesive is in the display, this UV absorbing function may interfere with the user's ability to further cure the adhesive using UV irradiation. Reducing the use of post-lamination curing processes not only limits the ability of the adhesive to balance compliance with rugged life reliability, but also generally limits the adhesive and mechanical performance properties of the OCA. Therefore, some recent technological developments in OCA materials have been developed to produce a potential curing mechanism that can be triggered with radiation in the visible spectrum so as not to compete with the UV blocking function. However, this functionality may make the potential curing chemistry more sensitive to ambient light during the integrated processing and lamination stages, which is undesirable.
[0039] OCAs are typically delivered to users as die-cut components between release liner carriers. When each surface of the OCA is laminated to a different portion of a display construction, the liner is peeled off in a subsequent step during the integration process. The present disclosure pairs the OCA with a release liner that protects the OCA from specific wavelengths that would prematurely activate the cure. In some cases, the OCA is a UV blocking, visible light curable OCA. The liner can be used to protect the underlying curing mechanism during shipping and handling of the adhesive die-cut components, and can also be used to protect the underlying curing mechanism during an integration process, such as a process in which the adhesive is laminated to one side of a display construction when the assembly is further processed in a manufacturing facility.
[0040] Release liner
[0041] In a first aspect, a release liner is provided. The release liner comprises:
[0042] a) a substrate having a first major surface and an opposing second major surface; and
[0043] b) a release coating disposed on at least a portion of the first major surface of the substrate,
[0044] Wherein at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°, the release liner transmits greater average incident light in a wavelength range of 470 nanometers (nm) to 530 nm than in a wavelength range of 400 nm to 460 nm.
[0045] In some cases, the release liner transmits at least 10% more average incident light in the wavelength range of 470nm to 530nm than in the wavelength range of 400nm to 460nm (at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°), transmits 15%, 20%, 25%, 30%, 35%, or at least 40% more average incident light in the wavelength range of 470nm to 530nm than in the wavelength range of 400nm to 460nm; and transmits up to 90% more average incident light in the wavelength range of 470nm to 530nm than in the wavelength range of 400nm to 460nm.
[0046] See also Figure 1 The release liner 100 includes a substrate 12 having a first major surface 11 and an opposite second major surface 13 , and a release coating 14 disposed on at least a portion of the first major surface 11 of the substrate 12 .
[0047] Typically, the substrate includes a polymer film. Exemplary suitable substrate materials include, for example, but not limited to, polyimide, polyethylene terephthalate (PET), polypropylene (PP), biaxially oriented polypropylene (BOPP), polyethylene (PE), polylactic acid (PLA), polymethyl methacrylate (PMMA), polyethylene naphthalate (PEN), polyurethane, polyvinyl chloride (PVC), polyvinyl alcohol (PVA), polyvinyl butyral, cellulose acetate, or any combination thereof. In some cases, preferred substrate materials include PET, PE, PP and / or BOPP.
[0048] Typically, polyimides have a yellow coloration and are therefore not completely transparent to visible light. For example, yellow materials typically absorb light in the range of 420nm to 430nm. It has been unexpectedly discovered that a release liner comprising a substrate containing polyimide effectively blocks (e.g., absorbs) at least some wavelengths that would prematurely activate adhesive curing, while still being sufficiently transparent for adhesive quality control monitoring and defect inspection by polyimide (e.g., for particles and / or bubbles in the adhesive, such as using optical equipment). In some applications, polyimide may be a preferred substrate material.
[0049] Many polymeric materials lack sufficient wavelength absorption to prevent premature adhesive curing. However, one or more light absorbers can be used in combination with a (e.g., transparent) substrate to impart desired light absorption properties to the release liner substrate. Polymeric substrate materials that can be used with light absorbers include, for example, PET, PP, BOPP, PE, PLA, PMMA, PEN, polyurethane, PVC, PVA, polyvinyl butyral, and cellulose acetate, to name a few.
[0050] For example, the light absorber may be incorporated into the substrate or present in a coating on the second major surface of the substrate (as opposed to a release coating). Figure 1 , a coating 16 including a light absorber is disposed on at least a portion of the second major surface 13 of the substrate 12. Useful light absorbers may include light absorber additives including dyes, pigments, red-shifted ultraviolet absorbers, nanoparticles (e.g., inorganic nanoparticles), or any combination thereof. A typical light absorber additive loading in the polymer material is 2 wt % to 10 wt % of the total weight of the substrate and the light absorber additive.
[0051] For example, suitable light absorber additives include commercial products such as "TINUVIN CARBOPROTECT" (BASF, Florham Park, NJ) or dyes such as tartrazine (Fischer Scientific, Waltham, MA) and sodium copper chlorophyllin (TCI Chemicals, Tokyo, Japan), to name a few. Exemplary suitable nanoparticles include carbon black, titanium dioxide, zinc oxide, cesium dioxide, zirconium dioxide, or combinations thereof. In addition to absorbing radiation, these particular nanoparticles often also have stability to ultraviolet radiation.
[0052] Some suitable red-shifted UV absorbers (RUVAs) absorb at least 70% (in some embodiments, at least 80% or even greater than 90%) of UV light in the wavelength region of 180 nm to 430 nm. RUVAs typically have enhanced spectral coverage in the long-wave UV region, making them capable of blocking high-wavelength UV light. One of the most effective RUVAs is the benzotriazole compound, 5-trifluoromethyl-2-(2-hydroxy-3-α-cumyl-5-tert-octylphenyl)-2H-benzotriazole (available from BASF under the trade name "CGL-0139"). Other exemplary benzotriazoles include 2-(2-hydroxy-3,5-di-α-isopropylphenyl)-2H-benzotriazole, 5-chloro-2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-2H-benzotriazole, 5-chloro-2-(2-hydroxy-3,5-di-tert-butylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-α-isopropylphenyl-5-tert-octylphenyl)-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-methylphenyl)-5-chloro-2H-benzotriazole. Other exemplary RUVAs include 2(-4,6-diphenyl-1-3,5-triazin-2-yl)-5-hexyloxy-phenol. Other exemplary UV absorbers include those available from BASF under the trade names "TINUVIN 1577", "TINUVIN 900", "TINUVIN 1600", and "TINUVIN 777". Other exemplary UV absorbers are available, for example, in polyester masterbatches under the trade name "TA07-07 MB" from Sukano Polymers Corporation, Duncan, SC. An exemplary UV absorber for polymethyl methacrylate is a masterbatch available, for example, from Sukano Polymers Corporation under the trade name "TA11-10MBO1".
[0053] There is no specific restriction on the release coating used in the release liner. Generally, the release coating includes a material selected from the group consisting of fluorine-containing materials, silicone-containing materials, fluorine-containing polymers, silicone polymers, fluorosilicone polymers, and poly (meth) acrylates derived from monomers including (meth) alkyl acrylates, wherein the (meth) alkyl acrylates have alkyl groups with 12 to 36 carbon atoms. In one embodiment, the alkyl group on the (meth) alkyl acrylate can be branched. Exemplary examples of available fluorine-containing polymers and silicone polymers can be found in U.S. Patent No. 4,472,480 (Olson), U.S. Patent No. 4,567,073 and U.S. Patent No. 4,614,667 (both Larson et al.). Exemplary examples of available poly (meth) acrylates can be found in U.S. Patent Application Publication No. 2005 / 118352 (Suwa). The release coating can be applied to the substrate by a solvent or solvent-free method.
[0054] Preferably, the release liner according to the present disclosure absorbs at least 10% of the incident light in the wavelength range of at least 400nm to 450nm at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°. In selected embodiments, the exemplary release liner transmits at least 30%, 35%, 40%, 45%, or at least 50% of the incident light in the wavelength range of 500nm to 595nm at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°; and transmits at most 90%, 85%, 80%, 75%, or at most 70% of the incident light in the wavelength range of 400nm to 450nm.
[0055] Adhesive products
[0056] In a second aspect, an adhesive article is provided. The adhesive article comprises:
[0057] a) a release liner, the release liner being according to any one of the embodiments of the release liner of the first aspect described in detail above; and
[0058] b) an optically clear adhesive disposed on at least a portion of the release liner.
[0059] See also Figure 2, adhesive article 200 includes a release liner 21 and an optically clear adhesive 26 disposed on at least a portion of the release liner 21. The release liner 21 includes: a substrate 22 having a first major surface 31 and an opposing second major surface 33; and a release coating 24 disposed on at least a portion of the first major surface 31 of the substrate 22. The optically clear adhesive 26 is located on at least a portion of the first major surface 37 of the release coating 24 of the release liner 21. Typically, the layer of optically clear adhesive 26 has a thickness in the range of 100 microns to 250 microns (in some embodiments, in the range of 125 microns to 200 microns), but other thicknesses are also useful.
[0060] In some embodiments, release liner 21 is a first release liner, and adhesive article 200 includes a second release liner 23 disposed on optically clear adhesive 26, opposite first release liner 21. In some cases, second release liner 23 differs from first release liner 21 in some aspects of its construction (e.g., a specific substrate and / or release coating), while in other cases, second release liner 23 is the same as the first release liner (e.g., according to any of the embodiments of the first aspect described in detail above). For example, Figure 2 The second release liner 23 depicted in the figure includes: a substrate 25 having a first major surface 41 and an opposite second major surface 43; and a release coating 28 disposed on at least a portion of the first major surface 41 of the substrate 25. The optically clear adhesive 26 has a first major surface 45 opposite to the first major surface 37 of the release coating 24 of the release liner 21, and the release coating 28 of the second release liner 23 is in contact with the first major surface 45 of the optically clear adhesive 26 opposite to the substrate 25 of the second release liner 23.
[0061] In some cases, it is advantageous to include two release liners that block at least some incident light in the wavelength range of 400 nm to 460 nm, particularly when the adhesive article may be exposed to ambient light prior to use in an article. In other cases, only one release liner that blocks such incident light is required because in some applications, the second release liner is quickly removed and the optically clear adhesive is adhered to the article, which itself can block at least some incident light in the wavelength range of 400 nm to 460 nm.
[0062] Preferably, the optically clear adhesive has a haze value of less than 7%, less than 5%, less than 2%, or less than 1% for a 0.1 mm thick optically clear adhesive coating (e.g., layer). The haze value is measured using a haze meter (available from BYK-Gardner, Columbia, MD, under the trade designation "HAZE-GARD PLUS").
[0063] Optionally, the optically clear adhesive (OCA) is a pressure sensitive adhesive. In certain embodiments, suitable OCAs are selected from acrylates, polyurethanes, polyolefins (such as polyisobutylene (PIB)), silicones, or combinations thereof. Exemplary OCAs include those described in: International Publication No. WO 2008 / 128073 (Everaerts et al.) for antistatic optically clear pressure-sensitive adhesives; U.S. Patent Application Publication No. US 2009 / 089137 (Sherman et al.) for stretch-release OCAs; US 2009 / 0087629 (Everaerts et al.) for OCAs compatible with indium tin oxide; US 2010 / 0028564 (Cheng et al.) for antistatic optical constructions with light-transmitting adhesives; US 2010 / 0040842 (Everaerts et al.) for adhesives compatible with corrosion-sensitive layers; US 2011 / 0126968 (Dolezal et al.) for optically clear stretch-release tapes; and U.S. Patent No. 8,557,378 (Yamanaka et al.) for stretch-release tapes. Suitable OCAs include acrylic optically clear pressure sensitive adhesives such as, for example, 3M OCA 8146, 8211, 8212, 8213, 8214, and 8215, each available from 3M Company, St. Paul, MN.
[0064] In some embodiments, suitable optically transparent adhesives include (meth) acrylate copolymers and reactive crosslinkers. Exemplary reactive crosslinkers include multifunctional components, such as multifunctional acrylates. The term "multifunctional" as used herein refers to a crosslinker having two or more ethylenically unsaturated groups that can be free radically polymerized. Specifically, available multifunctional crosslinkers include those selected from the group consisting of diols (such as butanediol), triols (such as glycerol) and tetraols (such as pentaerythritol) acrylates or methacrylates. Other available crosslinkers include those selected from the group consisting of other multifunctional vinyl compounds and multifunctional acrylated oligomers. Preferred crosslinking agents include those selected from the group consisting of multifunctional (meth)acrylates, for example, 1,4-butanediol diacrylate or 1,6-hexanediol diacrylate; pentaerythritol tetraacrylate; polyvinyl crosslinkers, such as substituted and unsubstituted divinylbenzene, polybutadiene diacrylate or polyisoprene diacrylate; and difunctional aminocaproate acrylates, such as "EBECRYL 270" and "EBECRYL 230" (acrylated polyurethanes of 1500 weight average molecular weight and 5000 weight average molecular weight, respectively, both available from Allnex, Alpharetta, Georgia).
[0065] In some embodiments, suitable optically clear adhesives include (meth)acrylate copolymers having pendant (meth)acryloyl groups and optionally pendant hydroxyl groups (e.g., compounded with a free radical generating photoinitiator). The (meth)acrylate copolymers may have a weight average molecular weight of 50,000 to 600,000 Daltons and an average molecular weight between the (meth)acryloyl groups equal to at least 16,000 Daltons.
[0066] In some embodiments, the optically clear adhesive can withstand damage from ultraviolet radiation. For example, the optically clear adhesive may also include a UV absorber. For example, exemplary adhesives that are generally resistant to damage from ultraviolet radiation include silicone adhesives and acrylic adhesives containing UV stabilization / blocking additives. For example, U.S. Pat. No. 5,504,134 (Palmer et al.) describes the use of metal oxide particles with a size in the range of about 0.001 microns to about 0.2 microns (in some embodiments, in the range of about 0.01 microns to about 0.15 microns) to reduce the degradation of polymer substrates caused by ultraviolet radiation. U.S. Pat. No. 5,876,688 (Laundon) describes a method for producing micronized zinc oxide, which is small enough to be transparent when incorporated into paint products, coating products, finishing products, plastic products, cosmetics, etc. as UV blockers and / or scatterers, and micronized zinc oxide is very suitable for use in the present invention. These fine particles, such as zinc oxide and titanium oxide, which can attenuate UV radiation, are available from, for example, Kobo Products, Inc., South Plainfield, NJ, in a size range of 10 nm to 100 nm. Generally, suitable UV absorbers absorb at least in the wavelength range of 300 nm to 400 nm.
[0067] In light of the present disclosure, one skilled in the art can readily identify suitable photoinitiator compounds for use herein. Preferably, the photoinitiator is activated by light having a wavelength of at least 350 nm. In addition, it is preferred that the photoinitiator is activated by light having a wavelength of up to 750 nm. Therefore, it is preferred that the photoinitiator is activated by light having a wavelength in the range of 350 nm to 750 nm, preferably 380 nm to 700 nm, and more preferably 400 nm to 460 nm. That is, the photoinitiator can be activated by light having a wavelength in the range of 380 nm to 460 nm, and / or 400 nm to 430 nm, and / or 450 nm to 485 nm, and / or 450 nm to 495 nm.
[0068] Suitable photoinitiators may be selected from the group consisting of: Norrish type (I) free radical polymerization initiators, Norrish type (II) free radical polymerization initiators, and any combination or mixture thereof. Exemplary suitable photoinitiators include, for example, but not limited to, α-diketones and / or phosphine oxides, preferably selected from camphorquinone, acylphosphine oxides, phenylpropanedione, acrolein phosphine oxide, dibenzoyl, 1-phenyl-1,2-propanedione, and any mixture and combination thereof. In some cases, the photoinitiator is preferably camphorquinone.
[0069] In selected embodiments, the optically clear adhesive comprises a crosslinkable composition comprising:
[0070] a) (meth)acrylate polymer, the (meth)acrylate polymer comprising an alkyl (meth)acrylate monomer;
[0071] b) an acylphosphine oxide photoinitiator; and
[0072] c) a crosslinking monomer comprising at least two terminal groups selected from the group consisting of allyl, methallyl, or combinations thereof.
[0073] Such OCAs provide UV-absorbent and post-lamination curable OCA films produced using a scheme utilizing a combination of fast polymerizing acrylic monomers with slower reacting crosslinker compounds. This scheme allows for greater separation between the polymerization and crosslinking functions of the adhesive without the need for multi-wavelength emission equipment, while allowing both functions to be achieved in the presence of a UV absorber additive.
[0074] The (meth)acrylate polymers can be prepared using known polymerization methods from polymerizable components including alkyl (meth)acrylate monomers.
[0075] (Meth) acrylate monomer
[0076] Any suitable alkyl (meth)acrylate or mixture of alkyl (meth)acrylates may be used, provided that the glass transition temperature of the final (meth)acrylate polymer is sufficiently low (e.g., not greater than 20° C.). Some alkyl (meth)acrylate monomers may be classified as low T based on the glass transition temperature of the corresponding homopolymer. g Monomer. Low T measured from the corresponding homopolymer g The monomers generally have a T of no greater than 20°C, no greater than 10°C, no greater than 0°C, or no greater than -10°C. g .
[0077] Suitable low T gThe (meth) alkyl acrylate monomer includes, but is not limited to, non-tertiary alkyl acrylates, but may be alkyl methacrylates having a linear alkyl group of at least 4 carbon atoms. Specific examples of (meth) alkyl acrylates include, but are not limited to, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, sec-butyl acrylate, n-pentyl acrylate, 2-methylbutyl acrylate, n-hexyl acrylate, cyclohexyl acrylate, 4-methyl-2-pentyl acrylate, 2-methylhexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, 2-octyl acrylate, isooctyl acrylate, isononyl acrylate, isopentyl acrylate, n-decyl acrylate, isodecyl acrylate, n-decyl methacrylate, lauryl acrylate, isotridecyl acrylate, n-octadecyl acrylate, isostearyl acrylate, n-dodecyl acrylate, and combinations thereof. In some embodiments, low T g The alkyl (meth)acrylate is selected from the group consisting of 2-ethylhexyl acrylate, isooctyl acrylate, n-butyl acrylate, 2-methylbutyl acrylate, 2-octyl acrylate, and combinations thereof. Other suitable monomers include branched long chain acrylates such as those described in U.S. Pat. No. 8,137,807 (Clapper et al.). Additional suitable alkyl monomers include secondary alkyl acrylates such as those described in U.S. Pat. No. 9,102,774 (Clapper et al.).
[0078] Other alkyl (meth)acrylates that may be included in the polymerizable component are classified as high T based on the glass transition temperature of the corresponding homopolymer. g Monomer. High T g The monomers generally have a T greater than 30°C, greater than 40°C, or greater than 50°C when homopolymerized. g (i.e., the homopolymer formed from the monomer has a T greater than 30°C, greater than 40°C, or greater than 50°C g ). Some suitable high T g The alkyl (meth)acrylate monomer includes, for example, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl (meth)acrylate, cyclohexyl methacrylate, isobornyl (meth)acrylate, stearyl (meth)acrylate, and 3,3,5-trimethylcyclohexyl (meth)acrylate.
[0079] The amount of alkyl (meth)acrylate incorporated into the (meth)acrylate polymer can be any suitable amount up to 100 wt % based on the total weight of the (meth)acrylic polymerizable components. The amount of alkyl (meth)acrylate is typically at least 35 wt %, at least 40 wt %, at least 45 wt %, or at least 50 wt %.
[0080] If the (meth)acrylate alkyl ester is selected to include a high T g If the monomer is used in an amount greater than 40 wt % based on the total weight of the polymerizable components, the amount of the monomer is generally not greater than 40 wt % based on the total weight of the polymerizable components. That is, the amount may be in the range of 0 wt % to 40 wt % based on the total weight of the polymerizable components. If a higher amount is used, the total T of the (meth)acrylate polymer may be greater than 40 wt %. g May be too high. High T g The amount of alkyl (meth)acrylate monomer is generally no greater than 35 wt%, no greater than 25 wt%, or no greater than 15 wt%. If present, high T g The amount of alkyl (meth)acrylate monomer is typically at least 0.5 wt%, at least 1 wt%, at least 3 wt%, at least 5 wt%, or at least 10 wt%. g (Meth) alkyl acrylate monomers are usually added with a sufficiently low T g The (meth) acrylate monomer is used to form a T of not more than 20°C. g (Meth)acrylate polymers.
[0081] The alkyl (meth)acrylate monomers are typically selected to include low Tg monomers, such as those having a Tg of no greater than -10°C when measured as a homopolymer. g For example, the polymerizable component typically contains at least 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, or at least 70 wt%, and up to 95 wt%, 90 wt%, 85 wt%, 80 wt%, 75 wt%, or up to 70 wt% has a T of no greater than -10°C when measured as a homopolymer. g Low T g Monomer. This amount is based on the total weight of the polymerizable components.
[0082] When measured as a homopolymer, it has a T of not greater than -10°C g Suitable alkyl monomers include, but are not limited to, 2-ethylhexyl acrylate, isooctyl acrylate, n-butyl acrylate, 2-methylbutyl acrylate, 2-octyl acrylate, and combinations thereof.
[0083] In some preferred embodiments, the alkyl (meth)acrylate monomer may be selected from the group consisting of 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, hexyl acrylate, butyl acrylate, cyclohexyl acrylate, isobornyl (meth)acrylate, and combinations thereof.
[0084] Additional monomer
[0085] In some embodiments, the (meth)acrylate polymer may include a hydroxyl (meth)acrylate comonomer. Examples of suitable monomers include, but are not limited to, 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and the like. In some embodiments, the (meth)acrylate polymer comprises between about 0 and about 40 parts by weight, between about 5 and about 35 parts by weight, or between about 10 and about 30 parts by weight of a hydroxyl functional copolymerizable monomer.
[0086] In some embodiments, the (meth)acrylate polymer may include a non-hydroxyl functional polar copolymerizable monomer. Examples of suitable non-hydroxyl functional polar copolymerizable monomers include, but are not limited to, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, ether functional monomers such as 2-ethoxyethyl (meth)acrylate, 2-ethoxyethoxyethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, nitrogen-containing monomers such as acrylamide, methacrylamide, N-alkyl substituted and N,N-dialkyl substituted acrylamide or methacrylamide (wherein the alkyl group has up to 3 carbons), and N-vinyl lactam. Examples of suitable substituted amide monomers include, but are not limited to, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-morpholino (meth)acrylate, N-vinyl pyrrolidone, and N-vinyl caprolactam. In some embodiments, the (meth)acrylate polymer includes between about 0 and about 20 parts by weight, specifically between about 1 and about 15 parts by weight, and more specifically between about 1 and about 10 parts by weight of the polar copolymerizable monomer.
[0087] In some embodiments, the (meth)acrylate polymer may include vinyl esters, and in particular C1 to C10 vinyl esters. Examples of commercially available suitable vinyl esters include, but are not limited to, vinyl acetate, and VEOVA 9 or VEOVA 10 (available from Momentive Specialty Chemicals, New Smyrna Beach, Florida). Vinyl esters are typically added to the monomer mixture in an amount between about 1 part by weight and about 20 parts by weight, specifically between about 1 part by weight and about 15 parts by weight, and more specifically between about 1 part by weight and about 10 parts by weight. Other monomers, such as styrenic monomers, may also be used.
[0088] In some embodiments, the (meth)acrylate polymer may include a polar (meth)acrylate monomer. Examples of suitable polar (meth)acrylate monomers include, but are not limited to, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, tetrahydrofuranyl acrylate, acrylamide, N,N-dimethylacrylamide, N-vinyl pyrrolidone, and acrylic acid. In some embodiments, the (meth)acrylate polymer includes between about 0 parts by weight and about 50 parts by weight, specifically between about 5 parts by weight and about 45 parts by weight, and more specifically between about 10 parts by weight and about 40 parts by weight of the polar (meth)acrylate monomer.
[0089] In some embodiments, the (meth)acrylate polymer may include a monofunctional non-(meth)acrylate vinyl ester monomer. Examples of suitable monofunctional non-(meth)acrylate vinyl ester monomers include, but are not limited to, N-vinyl pyrrolidone, N-vinyl carbazole, vinyl acetate, and vinyl ether. In some embodiments, the (meth)acrylate polymer includes between about 0 parts by weight and about 15 parts by weight, specifically between about 1 part by weight and about 10 parts by weight, and more specifically between about 1 part by weight and about 8 parts by weight of the monofunctional non-(meth)acrylate vinyl ester monomer.
[0090] In some embodiments, the (meth)acrylate polymer may include a multifunctional (meth)acrylate monomer. Examples of available multifunctional (meth)acrylate monomers include, but are not limited to, di(meth)acrylates, tri(meth)acrylates, and tetra(meth)acrylates, such as, for example, 1,6-hexanediol di(meth)acrylate, poly(ethylene glycol) di(meth)acrylate, polybutadiene di(meth)acrylate, polyurethane di(meth)acrylate, and propoxylated glycerol tri(meth)acrylate, and mixtures thereof. If used, the multifunctional (meth)acrylate monomer is typically used in an amount of at least 0.01, 0.02, 0.03, 0.04, or 0.05 parts by weight, and up to 1, 2, 3, 4, or 5 parts by weight relative to 100 parts by weight of the total monomer content.
[0091] In some preferred embodiments, the (meth)acrylate polymer may include 0 wt % to 50 wt % (e.g., 10 wt % to 40 wt %) of a polar (meth)acrylate monomer selected from the group consisting of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, tetrahydrofuranyl acrylate, acrylamide, N,N-dimethylacrylamide, N-vinyl pyrrolidone, acrylic acid, and combinations thereof; and 0 wt % to 10 wt % (e.g., 0 wt % to 5 wt %) of a monofunctional non-(meth)acrylate vinyl monomer selected from the group consisting of N-vinyl pyrrolidone, N-vinyl carbazole, vinyl acetate, vinyl ether, and combinations thereof.
[0092] (Meth)allyl crosslinking monomer
[0093] The crosslinkable composition also comprises a crosslinking monomer comprising at least two terminal groups selected from allyl, (meth)allyl or a combination thereof. The allyl group has the structural formula H2C=CH-CH2-. It consists of a methylene bridge (-CH2-) connected to a vinyl group (-CH=CH2). Similarly, the (meth)allyl group is a substituent having the structural formula H2C=C(CH3)-CH2-.
[0094] In some embodiments, the crosslinking monomer does not contain a vinyl group, such as vinyl ether. Vinyl, also known as vinyl, is the functional group -CH=CH2, ie, an ethylene molecule (H2C=CH2) minus one hydrogen atom.
[0095] In one embodiment, the crosslinking monomer includes two (meth)allyl groups and a (meth)acrylate group. This type of crosslinking monomer is commercially available from Sartomer, Exton, PA under the trade name "SR 523". In some embodiments, the crosslinking monomer does not contain a (meth)acrylate group. The lower reactivity of the (meth)allyl group compared to the (meth)acrylate group can be improved to achieve an optimal amount of crosslinking, particularly when the adhesive is cured by (e.g., UV) radiation.
[0096] The crosslinking monomers generally have the formula:
[0097] (H2C=C(R 1 )(CH2) y ) x Z
[0098] Where R 1In some embodiments, y is hydrogen or methyl, Z is a heteroatom or a multivalent linking group, and x ranges from 2 to 6. In some embodiments, y is from 5 to 20. In some embodiments, x is 2 or 3. For embodiments in which the crosslinking monomer comprises a multivalent linking group, the linking group Z typically has a molecular weight of no greater than 1000 g / mol, and in some embodiments no greater than 500 g / mol, 400 g / mol, 300 g / mol, 200 g / mol, 100 g / mol, or 50 g / mol.
[0099] Various crosslinking monomers containing at least two allyl and / or (meth)allyl groups are commercially available. Although these materials contain allyl groups, in many embodiments, the same materials with (meth)allyl groups are available or can be synthesized. For example, (meth)allyl adipate can be prepared in the manner described in U.S. Patent Publication No. 2017 / 0037282 (Lipscomb et al.).
[0100] Useful acylphosphine oxide photoinitiators may include, for example, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide ("TPO") commercially available from IGM Resins USA Inc., Charlotte, North Carolina, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide ("BAPO") commercially available from IGM Resins USA Inc., Charlotte, North Carolina. In a preferred embodiment, the crosslinkable composition includes 0.05 pph to 5 pph (e.g., 1 pph) of the acylphosphine oxide photoinitiator relative to the (meth)acrylate polymer mixture.
[0101] Additional details and methods for making such optically clear adhesives can be found in commonly owned PCT Application Publication No. WO2022 / 243801 (Kim et al.).
[0102] In selected embodiments, the optically clear adhesive comprises a crosslinkable composition comprising:
[0103] a) (meth)acrylate polymer, wherein the polymer has a glass transition temperature of no greater than 30°C;
[0104] b) a crosslinker comprising a photoactive Type II photoinitiator and a polymerizable group selected from the group consisting of (meth)acrylate, allyl, and combinations thereof;
[0105] c) optionally, an acid generator; and
[0106] d) UV absorbing material represented by the following structure:
[0107]
[0108] Where: X 1 , X 2 , X 3 and X 4 Each of is independently a hydrogen atom, a hydrocarbyl group containing 1 to 15 carbon atoms, preferably 12 carbon atoms, or a heterohydrocarbyl group containing 1 to 15 carbon atoms, preferably 12 carbon atoms.
[0109] Additional details and methods for making such optically clear adhesives can be found in commonly owned PCT Application Publication No. PCT / IB2022 / 062645 (Kim et al.).
[0110] Typically, the release liner exhibits a peel force (from an optically clear adhesive) of 100 grams per 25 millimeters (g / 25 mm) or less, 50 g / 25 mm, 25 g / 25 mm, 15 g / 25 mm, or even 10 g / 25 mm or less at a peel speed of 12 inches per minute (30.48 cm / min). Such peel forces can be used to easily peel off the release liner and integrate the adhesive into the article. It should be understood that different types of adhesive articles can be designed to have different preferred peel characteristics. The peel force can be measured using the test method described in the following examples.
[0111] The optically clear adhesives described above are typically coated on release liners using conventional coating techniques modified for the particular substrate. For example, these adhesives can be applied to a variety of release liners by methods such as stencil printing, screen printing, roller coating, flow coating, dip coating, spin coating, spray coating, blade coating, and die coating. These various coating methods allow the optically clear adhesive to be placed on the release liner at varying thicknesses, thereby allowing the adhesive articles to be used more widely.
[0112] Exemplary embodiments
[0113] In a first embodiment, the present disclosure provides a release liner. The release liner includes: a substrate having a first major surface and an opposing second major surface; and a release coating disposed on at least a portion of the first major surface of the substrate. The release liner transmits greater average incident light in a wavelength range of 470 nanometers (nm) to 530 nm than in a wavelength range of 400 nm to 460 nm at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°.
[0114] In a second embodiment, the present disclosure provides a release liner according to the first embodiment, wherein the substrate comprises a polymer film.
[0115] In a third embodiment, the present disclosure provides a release liner according to the first embodiment or the second embodiment, wherein the substrate comprises polyimide, polyethylene terephthalate (PET), polypropylene (PP), biaxially oriented polypropylene (BOPP), polyethylene (PE), polylactic acid (PLA), polymethyl methacrylate (PMMA), polyethylene naphthalate (PEN), polyurethane, polyvinyl chloride (PVC), polyvinyl alcohol (PVA), polyvinyl butyral, cellulose acetate, or any combination thereof.
[0116] In a fourth embodiment, the present disclosure provides a release liner according to any one of the first to third embodiments, further comprising a light absorber additive incorporated into the substrate or present in the coating on the second major surface of the substrate.
[0117] In a fifth embodiment, the present disclosure provides a release liner according to the fourth embodiment, wherein the light absorber additive comprises a dye, a pigment, a red-shifted UV absorber, nanoparticles, or any combination thereof.
[0118] In a sixth embodiment, the present disclosure provides a release liner according to any one of the first to fifth embodiments, wherein the release coating comprises a material selected from the group consisting of a fluorine-containing material, a silicone-containing material, a fluorine-containing polymer, a silicone polymer, a fluorosilicone polymer, and a poly(meth)acrylate derived from a monomer including an alkyl(meth)acrylate, wherein the alkyl(meth)acrylate has an alkyl group having 12 to 36 carbon atoms.
[0119] In a seventh embodiment, the present disclosure provides a release liner according to any one of the first to sixth embodiments, which absorbs an average of at least 10% of incident light in a wavelength range of at least 400 nm to 450 nm at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°.
[0120] In an eighth embodiment, the present disclosure provides a release liner according to any one of the first to seventh embodiments, wherein the release liner transmits an average of at least 30% of incident light in a wavelength range of 500 nanometers (nm) to 595 nm and transmits an average of at most 90% of incident light in a wavelength range of 400 nm to 450 nm at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°.
[0121] In a ninth embodiment, the present disclosure provides an adhesive article comprising a release liner according to any one of the first to eighth embodiments and an optically clear adhesive disposed on at least a portion of the release liner.
[0122] In a tenth embodiment, the present disclosure provides an adhesive article according to the ninth embodiment, wherein the optically clear adhesive further comprises a UV absorber.
[0123] In an eleventh embodiment, the present disclosure provides an adhesive article according to the ninth embodiment or the tenth embodiment, wherein the optically clear adhesive further comprises a photoinitiator that is activated when exposed to light having a wavelength in the range of 400 nm to 460 nm.
[0124] In a twelfth embodiment, the present disclosure provides an adhesive article according to any one of the ninth to eleventh embodiments, wherein the optically clear adhesive comprises a (meth)acrylate copolymer and a reactive crosslinker.
[0125] In a thirteenth embodiment, the present disclosure provides an adhesive article according to the twelfth embodiment, wherein the (meth)acrylate copolymer has pendant (meth)acryloyl groups and optionally pendant hydroxyl groups.
[0126] In a fourteenth embodiment, the present disclosure provides an adhesive article according to the ninth embodiment, wherein the optically clear adhesive comprises a crosslinkable composition comprising: a (meth)acrylate polymer comprising an alkyl (meth)acrylate monomer; an acylphosphine oxide photoinitiator; and a crosslinking monomer comprising at least two terminal groups selected from the group consisting of: allyl, methallyl, or a combination thereof.
[0127] In a fifteenth embodiment, the present disclosure provides an adhesive article according to the ninth embodiment, wherein the optically clear adhesive comprises a crosslinkable composition comprising: a (meth)acrylate polymer having a glass transition temperature of no greater than 30° C.; a crosslinker comprising a photoactive Type II photoinitiator and a polymerizable group selected from the group consisting of: (meth)acrylate, allyl, and combinations thereof; optionally, an acid generator; and a UV absorbing material represented by the following structure:
[0128]
[0129] Where: X 1 , X 2 , X 3 and X 4Each of is independently a hydrogen atom, a hydrocarbyl group containing 1 to 15 carbon atoms, preferably 12 carbon atoms, or a heterohydrocarbyl group containing 1 to 15 carbon atoms, preferably 12 carbon atoms.
[0130] In a sixteenth embodiment, the present disclosure provides an adhesive article according to any one of the ninth to fifteenth embodiments, wherein the optically clear adhesive is a pressure sensitive adhesive.
[0131] In a seventeenth embodiment, the present disclosure provides an adhesive article according to any one of the ninth to sixteenth embodiments, wherein the optically clear adhesive has a haze value of less than 5%, less than 2%, or less than 1% for a 0.1 mm thick coating.
[0132] In an eighteenth embodiment, the present disclosure provides an adhesive article according to any one of the ninth to seventeenth embodiments, wherein the release liner exhibits a peel force of 100 grams per 25 millimeters (g / 25 mm) or less, 50 g / 25 mm, 25 g / 25 mm, 15 g / 25 mm, or 10 g / 25 mm or less at a peel speed of 12 inches / minute (30.48 cm / minute).
[0133] In a nineteenth embodiment, the present disclosure provides an adhesive article according to any one of the ninth to eighteenth embodiments, wherein the release liner is a first release liner, and wherein the adhesive article further comprises a second release liner disposed on the optically clear adhesive opposite to the first release liner.
[0134] In a twentieth embodiment, the present disclosure provides an adhesive article according to the nineteenth embodiment, wherein the second release liner is different from the first release liner.
[0135] In a twenty-first embodiment, the present disclosure provides an adhesive article according to the nineteenth embodiment, wherein the second release liner is according to any one of the first to eighth embodiments.
[0136] The following examples further illustrate the advantages and embodiments of the present invention, but the specific materials and amounts thereof mentioned in these examples, as well as other conditions and details, should not be construed as unduly limiting the present invention. Unless otherwise indicated, all parts and percentages are by weight.
[0137] Example
[0138] Unless otherwise indicated or readily apparent from the context, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight. Table 1 (below) lists the materials used in the examples and their sources.
[0139] Materials used in the examples
[0140]
[0141]
[0142] Test Method
[0143] Optical characteristics test
[0144] Transmission measurements were made using an ULTRASCANPRO spectrophotometer (HunterLab, Reston, VA) in transmission mode. For the samples measured, the 0.1 mm thick coated adhesive layer between the release coated carrier liners described in the following examples was cut to approximately 5 cm wide by 10 cm long. One of the carrier liners was removed and the sample was laminated to a piece of clear 1 mm thick LCD glass (Swift Glass, Elmira Heights, New York). The second carrier liner was removed and the sample was placed in the ULTRASCANPRO spectrophotometer to measure the transmittance and color through the glass / OCA assembly. The transmittance at the specific wavelength was recorded and listed in Table 3 below.
[0145] Gel content test
[0146] The gel content of the adhesive film was characterized by gravimetric analysis. Circular samples of the polymerized and polymerized and cured adhesive films (thickness: 0.1 mm, sample diameter: 25 mm) were loaded into a porous stainless steel container (McMaster-Carr, Elmhurst, Illinois; mesh size: 0.5 mm, width × length × height: 40 mm × 40 mm × 30 mm) with a known mass. The mesh container and adhesive film were weighed and then immersed in a glass jar (diameter × height: 70 mm × 85 mm) containing a 1:1 v / v mixture of ethyl acetate / isopropanol (about 60 mL). After 24 hours, the metal container and the remaining adhesive film were removed from the solvent tank and dried in a convection oven (DESPATCH, Minneapolis, MN) at 120°C for 3 hours to provide a solvent incubated and dried adhesive film. The mass of the adhesive film before and after solvent incubation was recorded after subtracting the mass of the empty cage from each value. The gel content test was performed twice for each sample, and the gel content values were averaged.
[0147] The gel content of each adhesive film was calculated as follows:
[0148]
[0149] Molecular weight analysis using GPC
[0150] The molecular weight distribution of compound is characterized using conventional gel permeation chromatography (GPC). GPC instrument is available from Waters Corporation (Milford, MA) in Milford, Massachusetts, USA and includes high pressure liquid chromatography pump (model 1515HPLC), automatic sample injector (model 717), UV detector (model 2487) and refractive index detector (model 2410). The chromatograph is equipped with two 5 microns of PL gel MIXED-D posts available from Varian Inc. (Palo Alto, CA) in Palo Alto, California, USA.
[0151] Polymer solution samples were prepared by dissolving the polymer or dried polymer sample in tetrahydrofuran at a concentration of 0.5% (weight / volume) and filtering the solution through a 0.2 micron polytetrafluoroethylene filter purchased from VWR International (West Chester, PA). The resulting sample was injected into the GPC and eluted at a rate of 1 ml / min through a column maintained at 35°C. The system was calibrated with polystyrene standards and a calibration curve was established using linear least squares analysis. The weight average molecular weight (Mw) and polydispersity index (weight average molecular weight (Mw) divided by number average molecular weight (Mn)) of each sample were calculated based on the standard calibration curve.
[0152] Peel force test from release liner
[0153] The liner peel force was tested by cutting a sample of the test sample 1.27 cm wide (1 / 2") and approximately 10 cm long using a sample razor cutter. The cut sample was applied longitudinally to a peel adhesion tester (IMASS) using 3M Double Coated Paper Tape 410M (available from 3M Company, St. Paul, Minnesota). The release liner was peeled from the adhesive at an angle of 180 degrees at either 30.5 cm / min (12" / min) or 228.6 cm / min (90" / min) and the release force was recorded by the adhesive peel tester. At least two samples were tested for each release liner at each speed and the average release value was reported. Since the sample contained two release liners, the release liner with the easier release force (RF02N for comparative example) was tested first, while the tighter release liner (RF22N for comparative example) was laminated to the 410M tape. After testing the easier release liner, a HOSTAPHAN 3SAC polyester film (available from Mitsubishi Polyester Films, Greer, South Carolina, approximately 5.08 cm wide and 15 cm long) was laminated to the 410M tape using a hand roller. The sample was removed from the 410M tape and laminated to the exposed adhesive using a new piece of 410M tape, this time with the 3SAC polyester film facing down and the tighter release liner facing up so it could be peel tested.
[0154] Preparation Example
[0155] Preparation Example 1
[0156] nBA (78 g), EHMA (10 g), HEA (8.0 g), ACM (4.0 g), VAZO 52 (0.1 g), PE1 (0.2 g) and EtOAc (100 g) were added to a glass bottle. The contents were mixed and sparged with nitrogen for 2 minutes, then sealed and placed in a 60°C LAUNDER-OMETER rotating water bath (SDL Atlas, Rock Hill, SC, USA) for 24 hours. After 24 hours, the sample was taken out of the LAUNDER-OMETER and cooled using ambient conditions. GPC was used to analyze the sample and Mw was found to be 410 kDa. IEM (0.25 g) was added to the solution and the jar was heated at approximately 60°C for 24 hours using a jar rolling device equipped with an IR heating lamp.
[0157] Preparation Example 2
[0158] A 40 wt% solids (dry solids) solution of V21 and SYL-OFF 7488 in heptane:MEK (80:20) was prepared. Pt Cat (120 ppm) and DAM (0.2 wt%) inhibitor were added to the solution. An equivalent mass of 3,000 g / mol was used for V21 and an equivalent mass of 76 g / mol was used for SYL-OFF 7488 to prepare a 40 wt% solution at a hydride to vinyl ratio of 1.30. 120 ppm Pt Cat and 0.2 wt% DAM inhibitor were based on dry solids only (V21 + SYL-OFF 7488).
[0159] After the solution is prepared, use it within a few hours of mixing. The release formulation is coated onto a 2 mil (50 um) polyimide film (DuPont Kapton, 50 μm, available from DuPont in Wilmington, Delaware) using a #3 formed Meyer rod (available from RD Specialties Inc., Webster, New York) and the hand spread is heat cured on an open panel in a solvent rated oven at 120°C for 30 seconds. The solids and Meyer rod are picked to a cured silicone release coating weight of about 1.0 g / m2. After aging for 1 week at 23°C and 50% relative humidity, the hand spread is ready for use.
[0160] Example
[0161] Adhesive coatings (AD1 and AD2) were prepared using functionalized polymers from Preparation Example 1. For AD1, 50 grams of the selected polymer solution of Preparation Example 1 was placed in a glass jar, followed by the addition of CN996 (5.0 pph, relative to the total weight of polymer in the solution), SR351 (5.0 pph), I-819 (1.0 pph), TINUVIN 928 (2.0 pph) and methanol (2.0 pph). The jar was sealed and rolled using a jar roller for at least 12 hours before coating. For AD2, the same procedure outlined above for AD1 was used except that TPO (1.0 pph) was added instead of I-819 (1.0 pph).
[0162] The sample solution was coated onto a 75 μm PET liner with a release coating (RF22N) via a knife coater and dried at room temperature for 5 minutes and then at 70°C for 30 minutes. The dry thickness of all sample coatings was 100 μm ± 10 μm. After drying, a second liner of a siliconized polyester film (RF02N) or a siliconized polyimide film from Preparation Example 2 was laminated to the top of the sample coating. Optical measurements were performed on the films laminated with siliconized PET or siliconized PI as described in "Optical Characteristics Test", and the results are shown in Table 2 below.
[0163] Table 2: Optical measurements of gasket and adhesive construction on LCD glass
[0164]
[0165] The peel force of the liner with the coated adhesive from Example 1 and the siliconized PI film from Preparation Example 1 or either siliconized PET liner was tested according to the "Peel Force Test from Release Liner" above and is listed in Table 3 below.
[0166] Table 3: Peel force from release liner
[0167] Adhesives liner Peel force 12" / min Peel force 90" / min AD1 Preparation Example 2 3.6 5.7 AD1 RF02N 1.3 5.0 AD1 RF22N 7.1 15.9
[0168] The samples were then placed in an aluminum pan with the RF02N liner down and exposed to two different types of visible light sources while gel content measurements were taken at set time periods as shown in Tables 4 and 5 below. The gel content was tracked to determine whether exposure to ambient visible light initiated a crosslinking reaction within the optical adhesive material. For EX 1 and CE 1, the samples were exposed to an LED bulb at a distance of approximately 60 cm for up to 10 hours. Table 4 describes the gel content results for EX 1 covered by the liner from Preparation Example 2 and CE 1 covered by a siliconized PET liner (RF22N).
[0169] Table 4: EX 1 and CE 1 under LED #1 exposure
[0170]
[0171] Table 5 describes the gel content results for EX 2 covered by the liner from Preparative Example 2 and CE 2 covered by a siliconized PET liner (RF22N). For these examples, LED light source #2 was utilized at a distance of approximately 60 cm for up to 24 hours.
[0172] Table 5: EX 2 and CE 2 under LED #2 exposure
[0173]
[0174] In both Tables 4 and 5, it is observed that the PI-based release film allows protection from premature crosslinking from exposure to various ambient light sources, while the typical siliconized PET liner does not.
[0175] Foreseeable modifications and alterations of the present invention will be apparent to those skilled in the art without departing from the scope and spirit of the present invention.The present invention should not be limited to the embodiments shown in this application for illustrative purposes.
Claims
1. A release liner, comprising: a) a substrate having a first major surface and an opposing second major surface; as well as b) a release coating disposed on at least a portion of the first major surface of the substrate, c) wherein the release liner transmits greater average incident light in the wavelength range of 470 nanometers (nm) to 530 nm than in the wavelength range of 400 nm to 460 nm at an incident light angle of at least one of 0°, 15°, 30°, 45°, 60°, or 75°.
2. The release liner of claim 1, wherein the substrate comprises a polymer film.
3. The release liner of claim 1 or claim 2, wherein the substrate comprises polyimide, polyethylene terephthalate (PET), polypropylene (PP), biaxially oriented polypropylene (BOPP), polyethylene (PE), polylactic acid (PLA), polymethyl methacrylate (PMMA), polyethylene naphthalate (PEN), polyurethane, polyvinyl chloride (PVC), polyvinyl alcohol (PVA), polyvinyl butyral, cellulose acetate, or any combination thereof.
4. The release liner of any one of claims 1 to 3, further comprising a light absorber additive incorporated into the substrate or present in a coating on the second major surface of the substrate.
5. The release liner of claim 4, wherein the light absorber additive comprises a dye, a pigment, a red-shifted UV absorber, nanoparticles, or any combination thereof.
6. An adhesive product, comprising: a) a release liner according to any one of claims 1 to 5, and b) an optically clear adhesive disposed on at least a portion of the release liner.
7. The adhesive article of claim 6, wherein the optically clear adhesive further comprises a UV absorber.
8. The adhesive article of claim 6 or claim 7, wherein the optically clear adhesive further comprises a photoinitiator that is activated when exposed to light having a wavelength in the range of 400 nm to 460 nm.
9. The adhesive article of any one of claims 6 to 8, wherein the optically clear adhesive comprises a (meth)acrylate copolymer and a reactive crosslinker.
10. The adhesive article of claim 9, wherein the (meth)acrylate copolymer has pendant (meth)acryloyl groups and optionally pendant hydroxyl groups.
11. The adhesive article of claim 6, wherein the optically clear adhesive comprises a crosslinkable composition comprising: a) (meth)acrylate polymer, the (meth)acrylate polymer comprising an alkyl (meth)acrylate monomer; b) an acylphosphine oxide photoinitiator; and c) a crosslinking monomer comprising at least two terminal groups selected from the group consisting of allyl, methallyl, or combinations thereof.
12. The adhesive article of claim 6, wherein the optically clear adhesive comprises a crosslinkable composition comprising: a) (meth)acrylate polymer, wherein the polymer has a glass transition temperature of no greater than 30°C; b) a crosslinker comprising a photoactive Type II photoinitiator and a polymerizable group selected from the group consisting of (meth)acrylate, allyl, and combinations thereof; c) optionally, an acid generator; and d) UV absorbing material represented by the following structure in: X 1 , X 2 , X 3 and X 4 Each of is independently a hydrogen atom, a hydrocarbon group containing 1 to 15 carbon atoms, preferably 12 carbon atoms, or a heterohydrocarbon group containing 1 to 15 carbon atoms, preferably 12 carbon atoms.
13. The adhesive article of any one of claims 6 to 12, wherein the optically clear adhesive is a pressure sensitive adhesive.
14. The adhesive article of any one of claims 6 to 13, wherein the release liner exhibits a peel force of 100 grams per 25 millimeters (g / 25 mm) or less, 50 g / 25 mm, 25 g / 25 mm, 15 g / 25 mm, or 10 g / 25 mm or less at a peel speed of 12 inches per minute (30.48 cm / min).
15. The adhesive article of any one of claims 6 to 14, wherein the release liner is a first release liner, and wherein the adhesive article further comprises a second release liner disposed on the optically clear adhesive opposite the first release liner.
16. The adhesive article of claim 15, wherein the second release liner is different from the first release liner.
17. The adhesive article of claim 16, wherein the second release liner is according to any one of claims 1 to 5.
Citation Information
Patent Citations
Acrylic release agent precursor, release agent article, and process for producing release agent article
US20050118352A1
Indium-tin-oxide compatible optically clear adhesive
US20090087629A1
Rapid deployment of training for company representatives in contact handling systems
US20090089137A1
Antistatic optical constructions having optically-transmissive adhesives
US20100028564A1
Adhesives compatible with corrosion sensitive layers
US20100040842A1